Archaeogeophysical exploration in Neuss‐Norf, Germany using electrical resistivity tomography and magnetic data. Issue 5 (13th August 2021) - Ibraheem, Ismael M.; Bergers, Rainer; Tezkan, Bülent
ABSTRACT: A combination of electrical resistivity tomography (ERT) and magnetic gradiometry was selected to examine a hypothesis concerning the presence of remains of one of the oldest archaeological churches in the Rhineland, located in Neuss‐Norf, Germany. The gradiometer survey was carried out to measure the vertical gradient of the magnetic field using a proton precession magnetometer along several profiles. The magnetic data were reduced to the magnetic pole; then analytic signal and power spectrum techniques were applied. The ERT survey was based on the magnetic results, and both Wenner and dipole–dipole configurations were employed to collect the apparent resistivity data along 12 ERT profiles. The field ERT data from these two arrays were merged into one dataset to form a non‐conventional mixed array. The robust (blocky) inversion technique was applied to the resistivity data in order to derive the two‐dimensional resistivity distribution of the subsurface. Despite the noisy surroundings, the magnetic survey was able to give an indication of potential walls of the ancient church in addition to several subsurface magnetic sources. Moreover, highly resistivity anomalies were observed within the first 1–2 m of the subsurface soil and were interpreted as possible remains of man‐made structures. This depth range was also confirmed by the spectral analysis of the magnetic data. A strong consistency between the two methods was observed in some locations of the site. In addition, the ERT measurements confirm and complement most of the magnetic results. We successfully detected anomalous zones that could be associated with the walls of at least one ancient church building in addition to several possible archaeological structures in the survey area.